Enhancing Workforce Stability: Examining The Influence of Job Satisfaction and Work Environment on Employee Turnover Intention - Nugraha, Riky; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study investigates how Job Satisfaction and Work Environment impact employees' turnover intention at PT. Nakama Berkah Sejahtera Karawang. Using a quantitative approach with a causal method, the research surveys the entire employee population of 60 people. Primary data were collected via questionnaires, and the analysis employed multiple regression and hypothesis testing. The findings indicate that both Job Satisfaction and Work Environment significantly influence turnover intention, with each factor individually contributing to the reduction of turnover. These insights highlight the importance of improving job satisfaction and work environment to reduce turnover. However, the research is limited to these two variables, and future studies are encouraged to expand by considering additional variables and examining potential mediator and moderator effects. This research provides valuable insights for companies seeking strategies to reduce turnover intentions.